On the numerical solution of identification hyperbolic-parabolic problems with the Neumann boundary condition - M.A. Ashyralyeva; M. Ashyralyev (Қарағанды университетінің хабаршысы. Математика сериясы, 2018)
In the present study, a numerical study for source identification problems with the Neumann boundary condition for a one-dimensional hyperbolic-parabolic equation is presented. A first order of accuracy difference scheme for the numerical solution of the identification problems for hyperbolic-parabolic equations with the Neumann boundary condition is presented. This difference scheme is implemented for a simple test problem and the numerical results are presented.